Anti-inflammatory Effects of Empagliflozin and Gemigliptin on LPS-Stimulated Macrophage via the IKK/NF-κB, MKK7/JNK, and JAK2/STAT1 Signalling Pathways - Nami Lee; Yu Jung Heo; Sung-E Choi; Ja Young Jeon; Seung Jin Han; Dae Jung Kim; Yup Kang; Kwan Woo Lee; Hae Jin Kim (Journal of Immunology Research)
Background. Sodium-glucose cotransporter 2 (SGLT2) and dipeptidyl peptidase-4 (DPP-4) inhibitors are glucose-lowering drugs whose anti-inflammatory properties have recently become useful in tackling metabolic syndromes in chronic inflammatory diseases, including diabetes and obesity. We investigated whether empagliflozin (SGLT2 inhibitor) and gemigliptin (DPP-4 inhibitor) improve inflammatory responses in macrophages, identified signalling pathways responsible for these effects, and studied whether the effects can be augmented with dual empagliflozin and gemigliptin therapy. Methods. RAW 264.7 macrophages were first stimulated with lipopolysaccharide (LPS), then cotreated with empagliflozin, gemigliptin, or empagliflozin plus gemigliptin. We conducted quantitative RT-PCR (qRT-PCR) to determine the most effective anti-inflammatory doses without cytotoxicity. We performed ELISA and qRT-PCR for inflammatory cytokines and chemokines and flow cytometry for CD80, the M1 macrophage surface marker, to evaluate the anti-inflammatory effects of empagliflozin and gemigliptin. NF-κB, MAPK, and JAK2/STAT signalling pathways were examined via Western blotting to elucidate the molecular mechanisms of anti-inflammation. Results. LPS-stimulated CD80+ M1 macrophages were suppressed by coincubation with empagliflozin, gemigliptin, and empagliflozin plus gemigliptin, respectively. Empagliflozin and gemigliptin (individually and combined) inhibited prostaglandin E2 (PGE2) release and COX-2, iNOS gene expression in LPS-stimulated RAW 264.7 macrophages. These three treatments also attenuated the secretion and mRNA expression of proinflammatory cytokines, such as TNF-α, IL-1β, IL-6, and IFN-γ, and proinflammatory chemokines, such as CCL3, CCL4, CCL5, and CXCL10. All of them blocked NF-κB, JNK, and STAT1/3 phosphorylation through IKKα/β, MKK4/7, and JAK2 signalling. Conclusions. Our study demonstrated the anti-inflammatory effects of empagliflozin and gemigliptin via IKK/NF-κB, MKK7/JNK, and JAK2/STAT1 pathway downregulation in macrophages. In all cases, combined empagliflozin and gemigliptin treatment showed greater anti-inflammatory properties.